Environments of galaxies in groups within the supercluster-void network - Lietzen H; Tempel E; Heinämäki P; Nurmi P; Einasto M; Saar E (EDP SCIENCES S A, 2022)
Conclusions. Our results suggest that the evolution of galaxies is affected by both, the group in which the galaxy resides and its large-scale environment. Galaxies in lower-density regions develop later than galaxies in similar mass groups in high-density environment